2021
DOI: 10.48550/arxiv.2111.12210
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

From Kepler to Newton: Explainable AI for Science

Abstract: The Observation-Hypothesis-Prediction-Experimentation loop paradigm for scientific research has been practiced by researchers for years towards scientific discoveries. However, with data explosion in both mega-scale and milli-scale scientific research, it has been sometimes very difficult to manually analyze the data and propose new hypothesis to drive the cycle for scientific discovery. In this paper, we discuss the role of Explainable AI in scientific discovery process by demonstrating an Explainable AI-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Rather than focusing on societal issues of AI, XAI provides practical techniques and tools that hold significant potential for scientific discovery and research [24], [266], [267]. Here, we categorize these works into three groups by their approaches of leveraging XAI techniques.…”
Section: Scientific Explorations As Model Explanationmentioning
confidence: 99%
“…Rather than focusing on societal issues of AI, XAI provides practical techniques and tools that hold significant potential for scientific discovery and research [24], [266], [267]. Here, we categorize these works into three groups by their approaches of leveraging XAI techniques.…”
Section: Scientific Explorations As Model Explanationmentioning
confidence: 99%
“…Feature Importance in Nonlinear Embeddings automatically determines the important features that revealed previously unknown scientific attributes. Li et al [ 16 ] showed that concepts similar to Kepler laws of planetary motion and the Newton law of universal gravitation can be obtained through XAI methods.…”
Section: Introductionmentioning
confidence: 99%
“…decreasing NN by16.9% can cause cardinal number (CD), DT, and JJ to decrease or stay unchanged. Although the change in NN does not contribute to flipping the result, the resultant changes of CD and DT are sufficient to flip the outcome.…”
mentioning
confidence: 99%
“…Feature Importance in Nonlinear Embeddings automatically determines the important features that revealed previously unknown scientific attributes. Li et al [16] showed that concepts similar to Kepler laws of planetary motion and the Newton law of universal gravitation can be obtained through XAI methods.…”
Section: Introductionmentioning
confidence: 99%